Urban mass transit system in Nigeria - Bolade, Tunji (Ibadan : Ibadan University Press, 1989)
This book contains a collection of the papers presented by academics, researchers and practitioners of the transport industry at a seminar. The objectives of the seminar were two-fold: to take stock and appraise the means of improving the national mass transit programme launched by the Federal Government in 1988.
The proceedings of a seminar on urban mass transit system in Nigeria held in Kaduna between 27 February and 1 March 1989, organize by the federal urban mass transit programme (FUMTP)
Includes bibliographical footnotes and index.
hza 31/01/2019
Loans
Keywords: Local transit; Nigeria